Determinants of influenza non-vaccination among Canadian children: insights from a nationwide survey - Alami, Abdallah; Dave, Sailly; Uhlik, Caren; Ebrahim, Marwa; Krewski, Daniel; Laroche, Julie (Frontiers in Public Health, 2024)
To identify determinants influencing Canadian parents' decision not to vaccinate their children aged 6 months to 17 years against seasonal influenza. METHODS: Data from the 2022 Childhood COVID-19 Immunization Coverage Survey, a national survey of approximately 10,500 Canadian parents/guardians and their children, was analyzed. The survey examined influenza vaccine coverage, parental perspectives on vaccines, reasons for hesitancy, and factors influencing immunization. Socio-demographic characteristics, including ethnicity, household income, working sector, educational attainment, and prevalence of chronic medical conditions among children were considered. Historical vaccine uptake and the impact of the COVID-19 pandemic on immunization decisions were also reviewed. Key determinants of non-vaccination in the 2021-2022 season were analyzed using multivariable logistic regression, with a statistical significance level set at p-value < 0•05. RESULTS: 70% of children aged 6 months to 17 years did not receive the seasonal influenza vaccine. Key predictors for non-vaccination included: residing in rural settings (aOR 1•35, 95% CI 1•13-1•60), parental education attainment of less than high school (aOR 2•48, 95% CI 1•24-4•97), and the absence of chronic medical conditions in children (aOR 1•34, 95% CI 1•34-1•91)• Other strong predictors included lower household income; deterrence due to the COVID-19 pandemic; and parental hesitancy stemming from concerns about the vaccine's safety, effectiveness, and by beliefs that their child was not at risk of contracting the influenza or severe consequences from the infection. CONCLUSION: This research underscores pivotal determinants of parental decisions not to vaccinate their children against seasonal influenza and sheds light on the impact of the COVID-19 pandemic. The results highlight the importance of addressing safety concerns and providing clear information to alleviate hesitancy.